Provenance and paleogeography of the Devonian Durazno Group, southern Parana Basin in Uruguay. (March 2016) - Uriz, N.J.; Cingolani, C.A.; Basei, M.A.S.; Blanco, G.; Abre, P.; Portillo, N.S.; Siccardi, A.
Abstract: A succession of Devonian cover rocks occurs in outcrop and in the subsurface of central-northern Uruguay where they were deposited in an intracratonic basin. This Durazno Group comprises three distinct stratigraphic units, namely the Cerrezuelo, Cordobés and La Paloma formations. The Durazno Group does not exceed 300 m of average thickness and preserves a transgressive-regressive cycle within a shallow-marine siliciclastic shelf platform, and is characterized by an assemblage of invertebrate fossils of Malvinokaffric affinity especially within the Lower Devonian Cordobés shales. The sedimentary provenance of the Durazno Group was determined using petrography, geochemistry, and morphological studies of detrital zircons as well as their U–Pb ages. Sandstone petrography of Cerrezuelo and La Paloma sequences shows that they have a dominantly quartz-feldspathic composition with a minor contribution of other minerals. Whole-rock geochemical data indicate that alteration was strong in each of the three formations studied; chondritic-normalized REE patterns essentially parallel to PAAS, the presence of a negative Eu-anomaly, and Th/Sc and La/Hf ratios point to an average source composition similar to UCC or slightly more felsic. Within the Cerrezuelo Formation, recycling of older volcano-metasedimentary sources is interpreted from Zr/Sc ratios and high Hf, Zr, and REE concentrations. U–Pb detrital zircon age populations of the Cerrezuelo and La Paloma formations indicate that the principal source terranes are of Neoproterozoic age, but include also minor populations derived from Mesoproterozoic and Archean-Paleoproterozoic rocks. A provenance from the Cuchilla Dionisio-Dom Feliciano, Nico Pérez and Piedra Alta terranes of Uruguay and southern Brazil is likely. This study establishes an intracratonic extensional tectonic setting during Durazno time. Considering provenance age sources, regional paleocurrent distributions and the established orogenic history recorded in SW Gondwana, we suggest that the basin fill was derived from paleohighs located in what is currently SE Uruguay. Graphical abstract: Highlights: The Devonian Durazno Group as part of the Paraná Basin was deposited in an extensional basin. Its provenance is determined by petrography, geochemistry and detrital zircon dating. U–Pb detrital zircon age populations indicate main sources related to the Neoproterozoic, whereas minor record Mesoproterozoic rocks. Provenance from the Cuchilla Dionisio-Dom Feliciano, Nico Pérez and Piedra Alta terranes (Uruguay-Brazil) is evident. Source rocks and paleogeographical implications in SW Gondwana are compared and discussed.